Behavior of Rocket Piles Embedded in Sand under Static and Quasi-Static Cyclic Loading - Mohamed Elsiragy; Waseim Azzam; Ali Basha (Salehan Institute of Higher Education, 2026)
Pile foundations used in marine and onshore structures are often exposed to repeated axial loading, which can reduce their capacity and increase settlement over time. To address this issue, this study aims to evaluate the performance of rocket piles in sand and to understand how modifying pile geometry can enhance axial capacity under both static and quasi-static cyclic loading. A series of 1-g physical model tests were carried out to investigate the influence of sand relative density, pile slenderness ratio (L/D), fin-length ratio (Lf/L), fin-width ratio (b/D), fin location along the shaft, and surface roughness (Ra) on load–settlement behavior. The experimental results show that adding fins to the pile shaft significantly increases ultimate load capacity and reduces settlement compared to conventional smooth piles. The improvement is particularly noticeable under quasi-static cyclic loading, where fins help mobilize greater shaft resistance and limit the accumulation of settlement. Furthermore, larger fin-width and fin-length ratios provide greater performance enhancement. The main contribution of this study is the experimental evaluation of rocket piles under cyclic conditions and the development of practical design charts that allow engineers to estimate load improvement and settlement reduction based on fin geometry and surface characteristics, offering a more economical and efficient foundation solution in sandy soils.